Association between friends' hesitancy and personal COVID-19 vaccine hesitancy among Chinese medical staff - Lili Huang; Weiwei Hu; Yanhong Jiang; Weiwen Hong (Taylor & Francis Group, 2024)
ABSTRACTCOVID-19 vaccine hesitancy remains problematic among healthcare workers. Social network influences may shape vaccine decision-making, but few studies have examined this in this critical workforce. We assessed the relationship between friends' COVID-19 vaccination attitudes and personal hesitancy among Chinese healthcare personnel. In December 2022-January 2023, a cross-sectional online survey was conducted at a tertiary hospital in China using WeChat. Of the 1832 healthcare personnel who were invited to answer the structured questionnaire, 613 (33.5%) samples had valid data for data analysis. Logistic regression examined the association between friends' hesitancy and participants' own hesitancy, adjusting for confounders. Of 613 healthcare workers included, 266 (43.4%) were hesitant. Those with hesitant friends had 6.34 times higher adjusted odds of hesitating themselves versus those without hesitant friends (95% CI 2.97-13.52). Strong associations persisted across subgroups. Chinese healthcare workers' COVID-19 vaccination hesitancy was highly influenced by perceived friends' attitudes. Fostering pro-vaccine social norms through trusted peer networks could help promote vaccine acceptance in this critical workforce.